Motivational correlates of sports and physical activity - Satinder Singh; Baljinder Singh Bal (Physical Education of Students, 2024)
Background and Study Aim. The motivational aspect of athletes' commitment to training is an important indicator of their sports performance. However, there is insufficient understanding of the subtle dynamics that determine this commitment. The purpose of the study is to explore how athletes' motivation relates to their training duration across different sports. It also aims to identify the impact of intrinsic, extrinsic, and amotivation on training hours and to predict athletes' training commitment.